Efficacy and Safety of Prophylactic Agents in Prevention of Retinopathy of Prematurity: A Systematic Review and Meta-analysis of Randomised Controlled Trials - Waleed T Batais; Nada O Taher; Abeer K Alhindi; Abdullah A Ghaddaf; Anas Alamoudi; Sarah A Al-Ghamdi; Jumanah J Homsi; Hashem S Almarzouki; Mansour A Qurashi (BMJ Open Ophthalmology)
Objective Retinopathy of prematurity (ROP) is a leading cause of preventable childhood blindness in preterm infants with low birth weight. The efficacy and safety of prophylactic agents, including vitamin A, propranolol and lipids, in reducing ROP incidence remain unclear. This systematic review and meta-analysis evaluated the effectiveness and safety of these agents in preventing ROP.Methods and Analysis A systematic search was conducted in Embase, MEDLINE and CENTRAL databases. Eight randomised controlled trials involving 1101 preterm infants were included. We assessed the incidence of ROP at any stage, severe ROP, adverse events and mortality. Subgroup analyses were performed for each prophylactic agent. Data were pooled using the inverse variance weighting method and reported as risk ratios (RRs) with 95% CI.Results No significant reduction in ROP incidence at any stage was found in the intervention groups compared with placebo (RR=0.83; 95% CI= (0.69 to 1.00); p=0.05; I²=0%). Lipids significantly reduced severe ROP incidence (RR=0.48; 95% CI= (0.28 to 0.80); p=0.005), while vitamin A (RR=1.14; 95% CI= (0.51 to 2.54); p=0.75) and propranolol (RR=0.69; 95% CI= (0.29 to 1.65); p=0.41) did not. There were no significant differences in adverse events (RR=0.83; 95% CI= (0.59 to 1.17); p=0.28) or mortality (RR=0.93; 95% CI= (0.67 to 1.30); p=0.68) across all groups.Conclusion Lipids show promise in reducing severe ROP in preterm infants, while vitamin A and propranolol were not effective. Further research is needed to confirm these findings and explore the potential role of lipids in clinical practice.